Stany depresyjne młodych matek a konceptualizacje macierzyństwa - Olejniczak, Elwira (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The article analyses selected posts published by young mothers in two private Facebook groups entitled Noworodki, niemowlaki, dzieci – wymiana doświadczeń (Newborns, toddlers, children – sharing experiences) and Karmienie piersią i między karmieniami (Breastfeeding and between feedings). The issue influencing the analysis is conceptualisation which is one of the basic concepts in cognitive linguistics. The result of linguistic reflection is the observation of ways for conceptualising motherhood that are associated with psychophysical problems and depressive states of women in the perinatal period. Due to the thematic and temporal scope of the material, 45 entries published in 2022 and 2023 concerning the most difficult experiences were described. The collected examples were assigned to one of six distinguished conceptualisations, each related to the poor psychophysical condition of mothers.